2007
DOI: 10.1038/sj.ki.5002275
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo programmed macrophages ameliorate experimental chronic inflammatory renal disease

Abstract: Macrophage infiltration of the kidney is a prominent feature associated with the severity of renal injury and progressive renal failure. To determine the influence of macrophages in renal disease models in the absence of endogenous T and B cells, we performed adoptive transfer of macrophages into severe combined immunodeficient (SCID) mice. In this study, macrophages were isolated from the spleens of BALB/c mice and stimulated with lipopolysaccharide to induce classically activated M1 macrophages or with inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
282
1
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 333 publications
(313 citation statements)
references
References 47 publications
21
282
1
6
Order By: Relevance
“…In contrast, inhibition of nuclear factor-κB, a regulator of macrophage functional differentiation, reprogrammes macrophages so that they become profoundly anti-inflammatory in settings where they would normally be classically activated and attenuate glomerular inflammation in vivo [35]. Furthermore, ex vivo manipulation of macrophages using specific cytokines confirmed that classically activated, M1 macrophages worsen chronic inflammatory adriamycin nephropathy, whereas alternatively activated M2 macrophages reduce histological disruption and functional injury [36]. Of note, in the heart Camargo et al [37] have [39] Glycerol-induced ARF (mouse) MSCs Enhanced tubular proliferation [68] IR (rat) Papilla LRCs Proliferation and incorporation [149] IR (mouse) Bone marrow No functional improvement, intrarenal cells are the main source of repopulating cell during repair [22] Folic acid-induced acute tubular injury (mouse) Bone marrow Intrinsic tubular cell proliferation accounts for repair after damage [150] Folic acid-induced acute tubular injury (mouse) Bone marrow 10% incorporation in tubules and G-CSF doubles this rate [151] IR (rat) MSCs Improved renal function and less injury [152] Cisplatin-induced renal failure (mouse) MSCs Accelerated tubular proliferation [153] UUO (mouse) Bone marrow macrophages Reduced renal fibrosis [41] IR (rat) MSCs Improved renal function, increased proliferation and decreased apoptosis [84] IR (rat) rKS56 (S3 segment outgrowth) Replace tubular and improve function [80] Glycerol-induced tubulonecrosis (mouse) Human CD133 + cells Homing and tubular integration [66] UUO (rat) Label-retaining cells (LRC) Proliferates, migrates and transdifferentiates into fibroblast-like cells [27] Cisplatin-induced renal failure (mouse) G-CSF ± M-CSF Improvement in renal function and prevention of renal tubular injury [154] Anti-Thy1.1 GN (rat) MSCs Increased glomerular proliferation and reduction in proteinuria [53] Col4α3 deficiency (mouse) MSCs Prevented loss of peritubular capillaries and reduced fibrosis but no increase in function or survival [24] Col4α3 deficiency (mouse) Bone marrow Partial restoration of expression of the type IV collagen α3 chain, improved histology and function [25] Col4α3 deficiency (mouse) MSCs Improved function and glomerular scarring and interstitial fibrosis reduced [155] UUO (mouse) BM Instertitial BM-derived cells do not contribute significantly to collagen synthesis after damage [74] Adriamycin-nephropathy (mo...…”
Section: Bone Marrow-derived Cellsmentioning
confidence: 96%
“…In contrast, inhibition of nuclear factor-κB, a regulator of macrophage functional differentiation, reprogrammes macrophages so that they become profoundly anti-inflammatory in settings where they would normally be classically activated and attenuate glomerular inflammation in vivo [35]. Furthermore, ex vivo manipulation of macrophages using specific cytokines confirmed that classically activated, M1 macrophages worsen chronic inflammatory adriamycin nephropathy, whereas alternatively activated M2 macrophages reduce histological disruption and functional injury [36]. Of note, in the heart Camargo et al [37] have [39] Glycerol-induced ARF (mouse) MSCs Enhanced tubular proliferation [68] IR (rat) Papilla LRCs Proliferation and incorporation [149] IR (mouse) Bone marrow No functional improvement, intrarenal cells are the main source of repopulating cell during repair [22] Folic acid-induced acute tubular injury (mouse) Bone marrow Intrinsic tubular cell proliferation accounts for repair after damage [150] Folic acid-induced acute tubular injury (mouse) Bone marrow 10% incorporation in tubules and G-CSF doubles this rate [151] IR (rat) MSCs Improved renal function and less injury [152] Cisplatin-induced renal failure (mouse) MSCs Accelerated tubular proliferation [153] UUO (mouse) Bone marrow macrophages Reduced renal fibrosis [41] IR (rat) MSCs Improved renal function, increased proliferation and decreased apoptosis [84] IR (rat) rKS56 (S3 segment outgrowth) Replace tubular and improve function [80] Glycerol-induced tubulonecrosis (mouse) Human CD133 + cells Homing and tubular integration [66] UUO (rat) Label-retaining cells (LRC) Proliferates, migrates and transdifferentiates into fibroblast-like cells [27] Cisplatin-induced renal failure (mouse) G-CSF ± M-CSF Improvement in renal function and prevention of renal tubular injury [154] Anti-Thy1.1 GN (rat) MSCs Increased glomerular proliferation and reduction in proteinuria [53] Col4α3 deficiency (mouse) MSCs Prevented loss of peritubular capillaries and reduced fibrosis but no increase in function or survival [24] Col4α3 deficiency (mouse) Bone marrow Partial restoration of expression of the type IV collagen α3 chain, improved histology and function [25] Col4α3 deficiency (mouse) MSCs Improved function and glomerular scarring and interstitial fibrosis reduced [155] UUO (mouse) BM Instertitial BM-derived cells do not contribute significantly to collagen synthesis after damage [74] Adriamycin-nephropathy (mo...…”
Section: Bone Marrow-derived Cellsmentioning
confidence: 96%
“…Macrophages exhibiting this AAM phenotype were found in the lung later than 100 days post infection (data not shown). A number of differences in chemokine expression have been described between classical and alternatively activated macrophages [13][14][15]. To further characterize the Mac3 hi CD11b hi hemosiderin-laden macrophages, we assessed CCL5, CXCL11 and CCL17 chemokine expression levels in sorted cells.…”
Section: Long-term Hemorrhaging and Alternative Macrophage Activationmentioning
confidence: 99%
“…Les macrophages M1, délétères, produisent des radicaux libres oxygénés et sécrètent des cytokines pro-inflammatoires telles que le TNF- et l'IL-1-. Ces produits étant toxiques pour les cellules résidentes rénales, ils contribuent ainsi à l'extension des lésions et à la progression de la fibrose (Figure 2) [6,7]. À l'inverse, les macrophages de type M2 exercent un rôle protecteur.…”
Section: Phase D'apparition Des Myofibroblastes : Un Pour Tous Tousunclassified
“…À l'inverse, les macrophages de type M2 exercent un rôle protecteur. En effet, bien qu'ils soient capables de produire du TGF- et de la MEC, phénomènes qui a priori sont associés à un effet pro-fibrosant, leur rôle principal est de réduire l'inflammation grâce à la sécrétion de cytokines antiinflammatoires comme l'IL-10 et l'IL-6 ( Figure 2) [6,7]. Ainsi Wang et al ont mis en évidence que le transfert de macrophages polarisés (Figure 1) [11].…”
Section: Phase D'apparition Des Myofibroblastes : Un Pour Tous Tousunclassified
See 1 more Smart Citation